2013
DOI: 10.1158/1078-0432.ccr-13-0163
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Melanomas Harbor BRAF and NRAS Mutations and Copy Number Changes Similar to Cutaneous and Mucosal Melanomas

Abstract: Purpose: Conjunctival melanoma is a rare but potentially deadly tumor of the eye. Despite effective local therapies, recurrence and metastasis remain frequent. Once the tumor has metastasized, treatment options are limited and the prognosis is poor. To date, little is known of the genetic alterations in conjunctival melanomas.Experimental Design: We conducted genetic analysis of 78 conjunctival melanomas, to our knowledge the largest cohort reported to date. An oncogene hotspot array was run on 38 samples, scr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
187
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(219 citation statements)
references
References 52 publications
13
187
1
4
Order By: Relevance
“…While in some studies NRAS mutated melanomas were reported to be significantly thicker and higher Clark's level than wt tumors [61,62,64,68] other reports could not confirm any association between NRAS mutation and tumor thickness [70,71]. Ulceration was reported to be lower in NRAS-mutated tumors in comparison to BRAF mutated tumors (9.7 versus 22.4%, respectively) [63] but no obvious effect of mutational status on the presence of ulceration was reported by others [68].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 96%
“…While in some studies NRAS mutated melanomas were reported to be significantly thicker and higher Clark's level than wt tumors [61,62,64,68] other reports could not confirm any association between NRAS mutation and tumor thickness [70,71]. Ulceration was reported to be lower in NRAS-mutated tumors in comparison to BRAF mutated tumors (9.7 versus 22.4%, respectively) [63] but no obvious effect of mutational status on the presence of ulceration was reported by others [68].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 96%
“…BRAF mutations were significantly rising in tumors located at the caruncle (66% BRAF vs. 0% NRAS and 33% wild-type; P=0.03) as well as tumors originating from melanocytic nevi (65% BRAF vs. 27% NRAS and 9% wild-type; P<0.001) [10]. So a close relationship of conjunctival melanoma was suggested to cutaneous and mucosal melanoma and therefore therapeutic options of metastatic cutaneous and mucosal melanomas should be taken into consideration including clinical trials of novel agents for this patient´cohort [10]. lamina propria, enlarged nuclei, eosinophilic nucleoli and nuclear inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In 22-50% of conjunctival melanomas a V599E (V600E sometimes called) BRAF mutation was detected [1,9,10]. Griewank et al identified BRAF mutations in 23 of 78 (29%) conjunctival melanomas, demonstrating the majority of BRAF mutations (n=21; 91%) were V600E (T1799A) mutations [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations